HUBUNGAN KESIAPAN ANAK DENGAN KEBERHASILAN TOILET TRAINING PADA ANAK USIA TODDLER - Iwanda Sari, Intan; Ekawaty, Fadliyana; Eka Saputra, Nofrans (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2020)
At the age toddler children experience anal phase in this phase children are required to complete their development tasks, children must be able to recognize the urge to release, hold and be able to communicate to their mothers when they want to defecate. At this stage maximum must be reached until the child is 3 years old. The task of this development will be successful if its supported by children's readiness both physically, psychologically, intellectually and the readiness parents. The purpose of this study was to determine the relationship between children's readiness with success of toilet training in toddler age. Type of quantitative research with the type of correlational. This study uses the Cross Sectional approach. The instrument used is a questionnaire. The population is 77 mothers who have toddler age, taking samples using the total sampling method. Results of the study showed that there was a relationship between children's readiness with success of toilet training in toddler-age in the TPA of Alam Barajo Jambi City with a p-value 0,000 (p <0.05). One of the efforts to improve success in toilet training is looking the readiness available to children.